Enhancing the understanding and insights of students and industry operators in process engineering principles via immersive 3D environments - Norton, C.; Cameron, I.; Crosthwaite, C.; Balliu, N.; Tade, Moses; Shallcross, D.; Hoadley, A.; Barton, G.; Kavanagh, J. (Elsevier, 2008)
This work differentiates itself from most educational based multimedia resources by catering for two distinct audience groups. The first group is undergraduate process engineering students in a number of Australian institutions, whereas the second group represents operational staff at the industrial facilities covered by the interface. This presents challenges in pedagogy, educational pitch, industrial relations and project management. The learning environment is based around spherical imagery of real operating plants coupled with interactive embedded activities and content. This Virtual Reality (VR) learning tool has been developed by applying aspects of relevant educational theory and proven instructive teaching approaches. Principles such as constructivism, interactivity, cognitive load and learner-centred design have been central considerations when constructing and structuring this resource. Structural challenges include determining a framework for the basic environment, the repository for the VR and activities, as well as the development of a learning platform arrangement to support self-directed learning in the interface. Some of the system's current functionality is demonstrated through snapshots of the screen configuration. Future developments within the interface are revealed. © 2008 Elsevier B.V. All rights reserved.